2014
DOI: 10.1021/ol500918t
|View full text |Cite
|
Sign up to set email alerts
|

Directed Additions of 2-Arylpyridines and Related Substrates to Cyclic Imines through Rhodium-Catalyzed C–H Functionalization

Abstract: Rhodium-catalyzed C-H functionalizations have been used for ortho-directed additions of 2-arylpyridines and (hetero)aryl-substituted pyrimidines, isoquinolines, and benzo[h]quinolones to cyclic imines. The resulting amino-functionalized products are formed in good to high yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(18 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…88 A range of electron-rich and poor 2-arylpyridines were efficient coupling partners, and 2-(2-thiophenyl)pyridine and 2-(2-benzofuranyl)pyridine also coupled in good yield. N -Pyridyl and pyrimidyl indoles were also effective coupling partners.…”
Section: Aldiminesmentioning
confidence: 99%
“…88 A range of electron-rich and poor 2-arylpyridines were efficient coupling partners, and 2-(2-thiophenyl)pyridine and 2-(2-benzofuranyl)pyridine also coupled in good yield. N -Pyridyl and pyrimidyl indoles were also effective coupling partners.…”
Section: Aldiminesmentioning
confidence: 99%
“…In 2014, the Bolm laboratory published a strategy for Rh(III)‐catalyzed C−H additions to cyclic imines 26 (Scheme ) . Interestingly, in their evaluation of different metal catalysts the authors found that a cationic Ru(II) catalyst system also provided the desired addition product but in only moderate yield.…”
Section: Direct C−h Bond Addition To Imines To Provide Racemic Productsmentioning
confidence: 99%
“…In 2014, the Bolm laboratory published a strategy for Rh(III)-catalyzed CÀH additions to cyclic imines 26 (Scheme 8). [13] Interestingly, in their evaluation of different metal catalysts the authors found that a cationic Ru(II) catalyst system also provided the desired addition product but in only moderate yield. Several heteroaromatic directing groups were effective for this transformation, including pyridine, pyrimidine and quinoline functionalities, and the functionalization of both aromatic and heteroaromatic CÀH bonds was demonstrated.…”
Section: Rh Catalysismentioning
confidence: 99%
“…[12] More importantly, this reaction provides a new methodology to access unusual complex building blocks for the preparation of diverse biologically active compounds (Scheme 1). [13] In an initial attempt, cyclic N-sulfonyl ketimine 1 a, benzaldehyde (2 a) and diphenyl acetylene (3 a) were tested under the early [3+2] reaction conditions. [11a] Despite good conversion regarding the A + B variant, we detected the A + B + C product 5 a, albeit in a very low yield (Table 1, entry 1).…”
mentioning
confidence: 99%
“…Among other anhydrides screened, Ac 2 O and trifluoroacetic acid (TFAA) also proved to be appropriate for the reaction (Table 1, entries 9-11). However, varying the ratio of (Boc) 2 O only improved the yield of the two-component byproduct 4 a (Table 1, entries [12][13][14][15]. It is worth noting that other solvents, such as toluene, methanol, AcOH, and DMF, turned out to be ineffective for the MCR (Table 1, entries 16-19).…”
mentioning
confidence: 99%